Light rather than iron controls photosynthate production and allocation in Southern Ocean phytoplankton populations during austral autumn - van Oijen, T.; van Leeuwe, M.A.; Granum, E.; Weissing, F.J.; Bellerby, R.G.J.; Gieskes, W.W.C.; de Baar, H.J.W. (Journal of Plankton Research, 2004)
The role of iron and light in controlling photosynthate production and allocation in phytoplankton populations of the Atlantic sector of the Southern Ocean was investigated in April-May 1999. The 14C incorporation into five biochemical pools (glucan, amino acids, proteins, lipids and polysaccharides) was measured during iron/light perturbation experiments. The diurnal Chl a -specific rates of carbon incorporation into these pools did not change in response to iron addition, yet were decreased at 20 µmol photons m-2 s-1, an irradiance comparable to the one at 20-45m in situ depth. This suggests that the low phytoplankton biomass encountered (0.1-0.6 µg Chl a L-1) was mainly caused by light limitation in the deep wind mixed layer (>40m). Regional differences in carbon incorporation rates were not found in spite of differences in phytoplankton species composition: at the Antarctic Polar Front, biomass was dominated by a diatom population of Fragilariopsis kerguelensis , whereas smaller cells, including chrysophytes, were relatively more abundant in the Antarctic Circumpolar Current beyond the influence of frontal systems. Because mixing was often in excess of 100m in the latter region, diatom cells may have been unable to fulfil their characteristically high Fe demand at low average light conditions, and thus became co-limited by both resources. Using a model that describes the 14C incorporation, the consistency was shown between the dynamics in the glucan pool in the field experiments and in laboratory experiments with an Antarctic diatom, Chaetoceros brevis . The glucan respiration rate was almost two times higher during the dark phase than during the light phase, which is consistent with the role of glucan as a reserve supplying energy and carbon skeletons for continued protein synthesis during the night.